Caldendrin and Calneurons—EF-Hand CaM-Like Calcium Sensors With Unique Features and Specialized Neuronal Functions - Mundhenk, Jennifer; Fusi, Camilla; Kreutz, Michael R. (Frontiers in Molecular Neuroscience, 2019)
The CaM-like Ca2+-sensor proteins caldendrin, calneuron-1 and -2 are members of the neuronal Calcium-Binding Protein (nCaBP)-family that evolved relatively late during vertebrate evolution. All three proteins are abundant in brain but show a strikingly different subcellular localization. Whereas caldendrin is enriched in the postsynaptic density (PSD), calneuron-1 and -2 accumulate at the trans-Golgi-network (TGN). Caldendrin exhibit a unique bipartite structure with a basic and proline-rich N-terminus while calneurons are the only EF-Hand CaM-like transmembrane proteins. These uncommon structural features come along with highly specialized functions of calneurons in Golgi-to-plasma-membrane trafficking and for caldendrin in actin-remodeling in dendritic spine synapses. In this review, we will provide a synthesis of available data on the structure and biophysical properties of all three proteins. We will then discuss their cellular function with special emphasis on synaptic neurotransmission. Finally, we will summarize the evidence for a role of these proteins in neuropsychiatric disorders.